Differential effects of internalizing behaviors on academic functioning for girls versus boys: An analysis of developmental cascades from elementary to high school. (May 2020) - Okano, Lauren; Jeon, Lieny; Crandall, AliceAnn; Riley, Anne
Abstract: Youth's academic and emotional functioning are closely related, yet little is known about the timing and direction of relationships involving internalizing problems, which are characterized by over control of emotions, anxiety, and depression as well as multiple aspects of academic achievement. This study addresses these gaps using data from the Study of Early Child Care and Youth Development ( N = 1, 048) to examine the processes by which problems in one domain of functioning lead to problems in another, known as a "cascade effect." Results of longitudinal structural equation modeling indicate (a) a direct and indirect negative cascade effect from girls' internalizing problems to their school achievement in high school, (b) a positive contemporaneous association of 9th grade boys' internalizing problems with their cognitive achievement; and (c) ways in which demographic characteristics and adolescent social and maturational processes account for variation in functioning yet do not alter the processes by which the emotional and academic functioning interact. Results are discussed with regard to identifiying adolescents' internalizing problems, gender differences in the effects of internalizing problems on academic functioning, timing of evidence-based interventions, and implications for mental health promotion among girls.